EXPLORING COMMUNICATION STRATEGIES IN SPEAKING PRACTICE AT SECOND GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL - Febriyano Ramadhan; Sumadi Sumadi; Edy Waloyo (IAIN Syekh Nurjati Cirebon, 2018)
Abstract: Speaking is complex skill which includes ability to express ideas, intentions, and emotions of the speaker. Mastering speaking skill, students can convey and express their idea and meaning well. Speaking can be mastered by conducting practice in real conversation continuously, and one of the ways is through impromptu conversation designed by teacher. This research aims (1) to investigate communication strategy types employed by second grade students of XI MIPA 2 when performing impromptu conversation with peer in lesson asking and giving opinion with theme go shopping, and (2) to reveal factors that influence the use of particular types of communication strategies. This research applies descriptive qualitative design. Observation, interview, and documentation were carried out to collect the data to answer research questions. The findings show (1) students use five of nine communication strategies in Tarone (1980) taxonomy of communication strategies, namely language switch (36.93%), mime (27.02%), literal translation (22.52%), appeal for assistance (7.20%), and approximation (6.30%), and (2) the researcher reveals four factors that influence language switch; lack of vocabulary, pronunciation problem, interlocutor, and Indonesian term. Mime is influenced by three factors, such as simple and easy use, vocabulary difficulty, and interlocutor. Literal translation is caused by three factors, namely lack of grammatical knowledge, mother tongue influence, simple and easy use. Likewise, appeal for assistance has three factors; lack of vocabulary, pronunciation problem, and teacher instruction. Last, approximation is caused by two factors, such as conscious and unconscious factor.Keywords: Speaking practice, impromptu conversation, communication problems, communication strategies, second grade students.